Lemma 30.8.4. Let $S$ be a scheme. Let $n \geq 1$. Let $\mathcal{E}$ be a finite locally free $\mathcal{O}_ S$-module of constant rank $n + 1$. Consider the structure morphism

$\pi : \mathbf{P}(\mathcal{E}) \longrightarrow S.$

We have

$R^ q\pi _*(\mathcal{O}_{\mathbf{P}(\mathcal{E})}(d)) = \left\{ \begin{matrix} \text{Sym}^ d(\mathcal{E}) & \text{if} & q = 0 \\ 0 & \text{if} & q \not= 0, n \\ \mathop{\mathcal{H}\! \mathit{om}}\nolimits _{\mathcal{O}_ S}( \text{Sym}^{- n - 1 - d}(\mathcal{E}) \otimes _{\mathcal{O}_ S} \wedge ^{n + 1}\mathcal{E}, \mathcal{O}_ S) & \text{if} & q = n \end{matrix} \right.$

These identifications are compatible with base change and isomorphism between locally free sheaves.

Proof. Consider the canonical map

$\pi ^*\mathcal{E} \longrightarrow \mathcal{O}_{\mathbf{P}(\mathcal{E})}(1)$

and twist down by $1$ to get

$\pi ^*(\mathcal{E})(-1) \longrightarrow \mathcal{O}_{\mathbf{P}(\mathcal{E})}$

This is a surjective map from a locally free rank $n + 1$ sheaf onto the structure sheaf. Hence the corresponding Koszul complex is exact (More on Algebra, Lemma 15.28.5). In other words there is an exact complex

$0 \to \pi ^*(\wedge ^{n + 1}\mathcal{E})(-n - 1) \to \ldots \to \pi ^*(\wedge ^ i\mathcal{E})(-i) \to \ldots \to \pi ^*\mathcal{E}(-1) \to \mathcal{O}_{\mathbf{P}(\mathcal{E})} \to 0$

We will think of the term $\pi ^*(\wedge ^ i\mathcal{E})(-i)$ as being in degree $-i$. We are going to compute the higher direct images of this acyclic complex using the first spectral sequence of Derived Categories, Lemma 13.21.3. Namely, we see that there is a spectral sequence with terms

$E_1^{p, q} = R^ q\pi _*\left(\pi ^*(\wedge ^{-p}\mathcal{E})(p)\right)$

converging to zero! By the projection formula (Cohomology, Lemma 20.52.2) we have

$E_1^{p, q} = \wedge ^{-p} \mathcal{E} \otimes _{\mathcal{O}_ S} R^ q\pi _*\left(\mathcal{O}_{\mathbf{P}(\mathcal{E})}(p)\right).$

Note that locally on $S$ the sheaf $\mathcal{E}$ is trivial, i.e., isomorphic to $\mathcal{O}_ S^{\oplus n + 1}$, hence locally on $S$ the morphism $\mathbf{P}(\mathcal{E}) \to S$ can be identified with $\mathbf{P}^ n_ S \to S$. Hence locally on $S$ we can use the result of Lemmas 30.8.1, 30.8.2, or 30.8.3. It follows that $E_1^{p, q} = 0$ unless $(p, q)$ is $(0, 0)$ or $(-n - 1, n)$. The nonzero terms are

\begin{align*} E_1^{0, 0} & = \pi _*\mathcal{O}_{\mathbf{P}(\mathcal{E})} = \mathcal{O}_ S \\ E_1^{-n - 1, n} & = R^ n\pi _*\left(\pi ^*(\wedge ^{n + 1}\mathcal{E})(-n - 1)\right) = \wedge ^{n + 1}\mathcal{E} \otimes _{\mathcal{O}_ S} R^ n\pi _*\left(\mathcal{O}_{\mathbf{P}(\mathcal{E})}(-n - 1)\right) \end{align*}

Hence there can only be one nonzero differential in the spectral sequence namely the map $d_{n + 1}^{-n - 1, n} : E_{n + 1}^{-n - 1, n} \to E_{n + 1}^{0, 0}$ which has to be an isomorphism (because the spectral sequence converges to the $0$ sheaf). Thus $E_1^{p, q} = E_{n + 1}^{p, q}$ and we obtain a canonical isomorphism

$\wedge ^{n + 1}\mathcal{E} \otimes _{\mathcal{O}_ S} R^ n\pi _*\left(\mathcal{O}_{\mathbf{P}(\mathcal{E})}(-n - 1)\right) = R^ n\pi _*\left(\pi ^*(\wedge ^{n + 1}\mathcal{E})(-n - 1)\right) \xrightarrow {d_{n + 1}^{-n - 1, n}} \mathcal{O}_ S$

Since $\wedge ^{n + 1}\mathcal{E}$ is an invertible sheaf, this implies that $R^ n\pi _*\mathcal{O}_{\mathbf{P}(\mathcal{E})}(-n - 1)$ is invertible as well and canonically isomorphic to the inverse of $\wedge ^{n + 1}\mathcal{E}$. In other words we have proved the case $d = - n - 1$ of the lemma.

Working locally on $S$ we see immediately from the computation of cohomology in Lemmas 30.8.1, 30.8.2, or 30.8.3 the statements on vanishing of the lemma. Moreover the result on $R^0\pi _*$ is clear as well, since there are canonical maps $\text{Sym}^ d(\mathcal{E}) \to \pi _* \mathcal{O}_{\mathbf{P}(\mathcal{E})}(d)$ for all $d$. It remains to show that the description of $R^ n\pi _*\mathcal{O}_{\mathbf{P}(\mathcal{E})}(d)$ is correct for $d < -n - 1$. In order to do this we consider the map

$\pi ^*(\text{Sym}^{-d - n - 1}(\mathcal{E})) \otimes _{\mathcal{O}_{\mathbf{P}(\mathcal{E})}} \mathcal{O}_{\mathbf{P}(\mathcal{E})}(d) \longrightarrow \mathcal{O}_{\mathbf{P}(\mathcal{E})}(-n - 1)$

Applying $R^ n\pi _*$ and the projection formula (see above) we get a map

$\text{Sym}^{-d - n - 1}(\mathcal{E}) \otimes _{\mathcal{O}_ S} R^ n\pi _*(\mathcal{O}_{\mathbf{P}(\mathcal{E})}(d)) \longrightarrow R^ n\pi _*\mathcal{O}_{\mathbf{P}(\mathcal{E})}(-n - 1) = (\wedge ^{n + 1}\mathcal{E})^{\otimes -1}$

(the last equality we have shown above). Again by the local calculations of Lemmas 30.8.1, 30.8.2, or 30.8.3 it follows that this map induces a perfect pairing between $R^ n\pi _*(\mathcal{O}_{\mathbf{P}(\mathcal{E})}(d))$ and $\text{Sym}^{-d - n - 1}(\mathcal{E}) \otimes \wedge ^{n + 1}(\mathcal{E})$ as desired. $\square$

Comment #940 by correction_bot on

1. In the Koszul resolution, the term $\mathcal{E}(-1)$ should be $\pi^*(\mathcal{E})(-1)$

2. "In other to do this…", change other to order. Also, following this there are three occurrences of $-d+n+1$ where $-n-1-d$ is intended.

In your comment you can use Markdown and LaTeX style mathematics (enclose it like $\pi$). A preview option is available if you wish to see how it works out (just click on the eye in the toolbar).